Fuzzy nature and dynamic trust modeling in service oriented environments - Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S. (ACM, 2005)
In this paper, we propose and describe the six characteristics of trust. Based on the six proposed characteristics, we determine why trust is fuzzy. The term "fuzzy" in this paper not in the sense of the precise definitions given in the Fuzzy Systems literature but to indicate a certain vagueness, complexity or ill-definition and qualitative characterization rather than quantitative representation and dynamic. We then determine why due to the six characteristics of trust, trust is dynamic. We then propose a modelling language tool to model the fuzzy and dynamic nature of trust.